Oxygen sensors and neuronal adaptation to ischemia - Kunze, Reiner; Marti, Hugo (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.13938 Hugo H. Marti and Reiner Kunze
Published 15 December 2016
Gesehen am 10.10.2018